Assessment of interfacial fracture of asphalt mortar-aggregate system at low temperature: A study based on four-point bending test of sandwich beams. (17th October 2022) - Wu, Yumiao; Zhu, Xingyi; Liu, Chengbin; Dai, Ziwei
Highlights: Focus on the bonding region of asphalt mortar-aggregate system at low temperature. Four-point bending test with mortar-aggregate-mortar sandwich beam is executed. Failure mode of asphalt mortar-aggregate system is changed with temperatures. Effects of material types, aging level and aggregate roughness are considered. Abstract: The bonding properties of the asphalt mortar-aggregate interface at low-temperatures are investigated in this study. A novel method based on mortar-aggregate-mortar sandwich beam and four-point bending test is established. The effects of temperature, loading speed, material type, asphalt aging level and aggregate surface roughness on the bonding properties of the mortar-aggregate interface are methodically examined. Three cracking indexes, including peak bending stress, fracture energy and interface stiffness, are considered for the evaluation. It is concluded that the proposed testing method can effectively distinguish the low-temperature bonding performance of the asphalt mortar-aggregate system under different conditions. The obtained results reveal that the fracture energy can be increased by 700 % with the failure mode changing from brittle failure (−6 °C) to ductile failure (0 °C), and the positive correlation between loading speed and asphalt-mortar system fracture resistance at low temperature is verified. Additionally, the bonding properties are apparently affected by the type of asphalt and aggregate, aging level of the specimen, and aggregate surface roughness. Specimens composed of the styrene butadiene styrene (SBS) modified asphalt and basalt have the best bonding properties. The moderate aging of the specimen or increasing surface roughness of the aggregates has a positive incorporation into the bonding properties of the asphalt mortar-aggregate system, but severe aging or over-dense grooving act adversely.